Peran Mahasiswa KKN Dalam Membangun Kembali Semangat Gotong Royong di Masyarakat Aek Siansimun - Heka Maya Sari Sembiring; Nove Riski Manik; Rudolf Fourenjes Simamora; Ritasela Situmorang; Elsa Febbyola Sinuhaji; Ida Hotnauli Sinaga; Onima Lase; Nadia Christine Hasugian; Nomita Panjaitan (CV Putra Publisher, 2025)
The Real Work Lecture (KKN) students have successfully implemented the Desa Aek Siansimun, Kec. Tarutung, Kab. Tapanuli Utara, North Sumatra. Despite a number of challenges, successful outcomes have been made possible by effective community and student participation. Cleaning the environment, solving trash issues, and raising awareness of the value of cleanliness are all part of this cooperative activity. Students and inhabitants of Aek Siansimun, Tarutung District, North Tapanuli Regency, North Sumatra, develop a familial bond through this program in addition to its tangible effects. The success of this program depends on the active participation of the community. This curriculum for mutual cooperation helps students learn how to be socially and leadership-savvy. It is hoped that the program's success would serve as a motivational model for KKN's upcoming events and that it will continue to benefit the environment and society.